(untitled) (Educational Dimension, 2023)
The article is devoted to the study of the theoretical and organizational foundations of language teaching in the Canadian education system in the context of globalization processes and multilingual society. The work presents a retrospective analysis of the formation and development of language teaching in the Canadian education system from the beginning of organized education to the beginning of the 21st century, highlights certain issues of state regulation in the field of language education in Canada. The socio-political context of the development of multilingualism in Canada is analyzed and the stages of formation and development of a multilingual society are determined. The work reveals the peculiarities of the organization of L1, L2 and FL learning at various levels of the Canadian education system. The conceptual ideas of language learning in Canadian pedagogical research are defined; the specifics of language training of citizens in the Canadian education system, taking into account the bilingual nature of society, are identified; the newest methods and trends in development of language education in Canada are reviewed. On the basis of a comparison of the language training practice in Ukraine and Canada, certain elements of the positive Canadian experience have been identified, which are expedient to use in the national education system in the conditions of the creation of the European context of language education.